Effect of tocilizumab on pulmonary gas exchange function in patients with severe COVID-19 - D. A. Lebedev; Yu. Kh. Dolya; G. E. Savkov; M. A. Godkov; E. V. Klychnikova; А. P. Shakotko; D. A. Kosolapov; S. N. Kuznetsov; A. M. Kvasnikov; Yu. N. Vrabiy; K. V. Kiselev; V. B. Poluektova; et al. (Трансплантология (Москва), 2023)
Introduction. COVID-19 causes cytokine storm and acute respiratory distress syndrome, which can lead to severe lung damage and multiple organ dysfunction. Early use of monoclonal antibodies has shown promising results in cytokine storm therapy, but the effects on lung gas exchange function have not yet been studied.Aim. To evaluate the effect of tocilizumab on the dynamics of gas exchange parameters in patients with severe COVID-19. Material and methods. The study included 26 patients in whom gas exchange parameters (PaO2, PaCO2, P/f ratio), blood oxygen saturation (saturation), respiration rate, duration and parameters of high-flow oxygen therapy and noninvasive mechanical ventilation, length of stay in intensive care unit and total hospital length of stay were assessed.Results. Tocilizumab significantly improved oxygenation on the third day (p=0.001) from the time of drug administration.Conclusion. In the presented and analyzed cohort of patients with severe COVID-19 and cytokine storm, the normalization and significant increase of oxygenation parameters (PaO2, p=0.001; P/f ratio, p=0.001) were observed within three days after a single-dose tocilizumab administration in a complex intensive therapy. No significant dynamics in the respiratory support parameters was revealed, nor an effect of this therapy on the duration of the respiratory support or the reduction in the aggressiveness of its parameters was observed within three days after tocilizumab administration (p>0.05).